Effect of a Commercial NCLEX-RN Preparation Product on First Time Pass Rates - Lisa Scandale Lewis EdD, MSN, RN, CNE; Tonya Willingham EdD, MA, MSN, RN, CNE; John Myers PhD, MSPH; Daniel Hatch PhD (SAGE Open Nursing, 2023)
Introduction Passing the National Council Licensure Exam-Registered Nurse (NCLEX-RN) is the entry into the profession for nurses, and rates of passing the exam on the first attempt are used as an important outcome measure for schools, students, and accrediting agencies. Objective This study was conducted in order to investigate if a commercial NCLEX-RN test preparation product impacted first time pass rates. Methods Data were collected from 688 students from six institutions who were taking the NCLEX-RN for the first time. The intervention group (n = 396) received a 6-month subscription to a commercial product with which to prepare for the NCLEX-RN, and was compared to the control group (n = 292) to test for differences in demographics and test pass rates. Results The intervention group was more likely to be younger than 25 years of age (n = 160, 55.8% vs. n = 76, 34.6%; p  < .001) when compared with the control group. No other significant differences in demographics or NCLEX-RN pass rates were observed between the groups. Conclusion and Recommendations This study failed to demonstrate a change in the likelihood of passing NCLEX-RN on the first attempt in a group of students who used a commercial test preparation product. We recommend that instructor-guided use of a test-preparation product, along with other interventions to support test success, be considered in creating an individualized plan for nursing students preparing for NCLEX-RN.